Legal impact and urgency of protection for users of illegal online loan services - Sianjaya, Ivone Christy; Hasan, Tandyo; Susiawati, Andyna (The International Journal of Politics and Sociology Research, 2024)
This study aims to identify legal sanction against illegal lending providers in Indonesia and examine legal protection for users of illegal online loan services. The research method used is a normative legal approach with a focus on analysis of applicable laws and regulations. Indonesia has a number of legal sanctions that have been imposed on illegal loan organisers, including suspensions of operations, administrative sanctions, and even criminal penalties under the Law and OJK Regulations. These measures aim to protect the public from illegal practices that can harm them financially and socially. On the user side, legal protection is regulated by POJK 77/2016 and the Consumer Protection Law, which provides consumer protection facilities such as complaint services and legal defence. Even though there are regulations that have been implemented, illegal loan services remain a problem because they offer loans without official permission, take advantages of people’s lack of financial literacy, and create the risk of uncontrolled lending. The importance of understanding and complying with the rules and laws that apply in lending services is the key to avoiding legal risks and financial problems